School library research in Nigeria (2012)
"Purpose – The purpose of this article is to analyse the content of the Nigerian School Library Journal (NSLJ) from 1979-2010. Design/methodology/approach – This study adopts a descriptive research approach by means of bibliometric analysis. The NSLJ was examined for subject coverage, geographic distribution of authors, country of origin of authors, publication output, collaboration among authors, international visibility, gender of authors, research type, and language of articles. The international visibility of the journal was investigated through the web-based version of Ulrich’s Periodicals Directory, Africa Journals Online (AJOL) and literature search. Findings – There have been nine issues since the first publication in 1979. The study discovered that NSLJ was not listed among the known LIS journals from Nigeria. The geographical distributions and nationality of the authors in NSLJ indicated that all the authors were Nigerians, and the level of collaboration among the authors was low (16.7 per cent) while single authors were many (83.3 per cent). The study revealed that most articles used the survey research design followed by historical strategies, literature review and case studies. Practical implications – The NSLJ does not have the visibility it needs internationally; therefore the editors could aim to index the journal in renowned abstracting services. NSLJ editions should aim to get published on time using a quality peer review process and the journal should be listed with AJOL because increasing the visibility of the journal would assist in increasing the journal’s quality. Originality/value – The study has identified gaps in promoting school library research from Nigeria internationally, and in the quality of Nigerian research that could be addressed by future studies "